Analysis of Coping Mechanisms on Student Resilience in Managing Academic Stress - Amalianita, Berru; Kusaini, Utami Niki; Yulianti, Yulianti; Zubaidah, Zubaidah; Putri, Yola Eka (Darul Yasin Al Sys, 2025)
This research is motivated by the fact that many students experience academic stress or are at risk of experiencing academic stress. The purpose of this study is to examine the effect of coping mechanisms on students' resilience in dealing with academic stress. The methodology used is a literature review, where the reviewed literature consists of previous studies relevant to this research. Based on the findings, it can be concluded that coping mechanisms influence students' resilience in facing academic stress. Students with effective coping mechanisms tend to have higher resilience in managing various academic demands.